2016
DOI: 10.1016/j.cbpc.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

ABC transporters and xenobiotic defense systems in early life stages of rainbow trout (Oncorhynchus mykiss)

Abstract: Embryos of oviparous fish, in contrast to (ovo) viviparous species, develop in the aquatic environment, and therefore need solute transport systems at their body surfaces for maintaining internal homeostasis and defending against potentially harmful substances. We hypothesized that solute transporters undergo changes in tissue distribution from the embryo to the larval stage. We therefore studied the mRNA profiles of eight ABC transporters (abcb1a, abcb1b, abcc1, abcc2, abcc3, abcc4, abcc5, abcg2) and three so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 68 publications
1
18
0
Order By: Relevance
“…No significant change was observed for UGTs at 24 h under DCF exposure. Kropf et al also found the mRNA expression of UGTs had changes but no significant differences in early life stages of rainbow trout (Kropf et al, 2016), similar to the UGT performance in the present study. But with the prolonged exposure time, UGT gene expression exhibited inverted "U"-shape change pattern with rising concentrations at 168 h, and similar changes was observed in the livers of Nile tilapia (Thummabancha et al, 2016).…”
Section: Transcriptional Changes Ofsupporting
confidence: 89%
“…No significant change was observed for UGTs at 24 h under DCF exposure. Kropf et al also found the mRNA expression of UGTs had changes but no significant differences in early life stages of rainbow trout (Kropf et al, 2016), similar to the UGT performance in the present study. But with the prolonged exposure time, UGT gene expression exhibited inverted "U"-shape change pattern with rising concentrations at 168 h, and similar changes was observed in the livers of Nile tilapia (Thummabancha et al, 2016).…”
Section: Transcriptional Changes Ofsupporting
confidence: 89%
“…Additionally, RhB is detrimental to the environment with evidence of long lasting effects to aquatic life. 22 Despite being known as a carcinogenic compound, it is used illegally as a food dye in many countries. 23 Moreover, RhB is stable in water in a wide pH range and not biodegradable; therefore, it should be fully removed or decomposed before releasing RhB-containing wastewater to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Reports on fish Abcg1 are available only for zebrafish lipid metabolism and related human diseases (atherosclerosis and angiogenesis) ( Fang et al, 2013 , 2014 for a review). Abcg2 is the most studied member of this subfamily in fish as an essential protein concerning xenobiotics detoxification ( Paetzold et al, 2009 ; Kropf et al, 2016 ; Zaja et al, 2016 , among others). ( Zhang L. et al, 2020 ) characterized zebrafish abcg5 and abcg8.…”
Section: Abc Proteinsmentioning
confidence: 99%